Efektifitas Digital Storytelling dalam Meningkatkan Pemaafan (Forgiveness) pada Siswa Sekolah Dasar - Hafnidar Hafnidar; Nessa Aqila; Rahmi Mauliza; Rahmi Maghfirah; Ananda Nurisyahadah; Istiqomah Istiqomah (Journal on Education, 2025)
This study aims to examine the effect of digital storytelling on the forgiveness abilities of elementary school students. The subjects comprised 40 students divided into an experimental group (20 students) and a control group (20 students). The experimental group received a video intervention featuring the story of Prophet Yusuf. The study design employed a static group design. Data collection was conducted using a psychological scale based on McCullough's theory. The results showed that digital storytelling significantly enhanced forgiveness (p < 0.05) in the experimental group compared to the control group. This study indicates that innovative learning methods based on digital storytelling are effective in supporting the emotional development of elementary school students in increasing their ability to forgive.